I'm trying to take the (two-sided, aka defined for all n) Z-transform of

\[x(n)=sin(Bn)\]

What I tried to do was split x(n) into

\[x(n)=sin(Bn)u(n)+sin(Bn)u(-n-1)\]

But a problem arises now because the z-transform of the first equals the negative of z-transform of the second, which makes the z-transform = 0. Waaah? Could this be?

\[x(n)=sin(Bn)\]

What I tried to do was split x(n) into

\[x(n)=sin(Bn)u(n)+sin(Bn)u(-n-1)\]

But a problem arises now because the z-transform of the first equals the negative of z-transform of the second, which makes the z-transform = 0. Waaah? Could this be?

Last edited: